The use of CCCM for the creation of the high-temperature detectors of the water wapor - Gurin, I.; Ovcharenko, V.; Tokarieva, О.; Moshnik, O. (Problems of Atomic Science and Technology, 2023)
A technique for assessing the presence of water vapor in a mixture using high-temperature detectors made of carbon-carbon composite material (CCCM) is proposed. The change in the electrical resistance of CCCM in a mixture containing water vapor at a temperature of 1000 °C is presented. The efficiency of such detectors has been tested and experimentally confirmed.